2021
DOI: 10.1038/s41598-021-00431-2
|View full text |Cite|
|
Sign up to set email alerts
|

Nkx3-1 and Fech genes might be switch genes involved in pituitary non-functioning adenoma invasiveness

Abstract: Non-functioning pituitary adenomas (NFPAs) are typical pituitary macroadenomas in adults associated with increased mortality and morbidity. Although pituitary adenomas are commonly considered slow-growing benign brain tumors, numerous of them possess an invasive nature. Such tumors destroy sella turcica and invade the adjacent tissues such as the cavernous sinus and sphenoid sinus. In these cases, the most critical obstacle for complete surgical removal is the high risk of damaging adjacent vital structures. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 109 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…The random forest algorithm offers various metrics for assessing variable importance, among which Mean Decrease Accuracy (MDA) is considered the most reliable. MDA determines importance by evaluating the reduction in classification accuracy when the expression values of a particular gene are randomly permuted 18 , 19 . In our study, we utilized MDA to identify the important switch genes, as presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The random forest algorithm offers various metrics for assessing variable importance, among which Mean Decrease Accuracy (MDA) is considered the most reliable. MDA determines importance by evaluating the reduction in classification accuracy when the expression values of a particular gene are randomly permuted 18 , 19 . In our study, we utilized MDA to identify the important switch genes, as presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…So far, the three-way interaction approach has been employed to deciphering the pathogenesis of several diseases, including inflammatory diseases 18 , 19 . The importance of RT-DOb /{ Csf1r , Milr1 } triplet in onset of Alzheimer’s disease has been suggested and validated in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have shown that changes in FECH expression were detected in human colon cancers and that loss of FECH has a tumor-suppressive effect on colon carcinogenesis in vitro [ 26 ], which was a potential tumor-suppressor gene for colon cancer [ 27 ]. The FECH gene may be a switch gene involved in the invasiveness of pituitary nonfunctioning adenomas [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, putative switch mechanisms involved in triggering Alzheimer's disease (AD) were detected using a three-way interaction model [10]. Use of three-way interaction models, including the liquid association model that was used in the earlier study, is an efficient approach for finding switch mechanisms [10][11][12][13][14]. In this model, it is assumed that there is a switch gene, say Z, which controls the co-expression of a gene pair, say {X 1 and X 2 }.…”
Section: Introductionmentioning
confidence: 99%